2019
DOI: 10.1177/0308022619840167
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapy student learning on role-emerging placements in schools

Abstract: Introduction: Placements are considered vital in promoting theory-to-practice learning. With role-emerging placements increasingly being offered, the learning processes experienced by students warrants further investigation. This research explored the learning experiences of students, from both supervisor and student perspectives, over the duration of a role-emerging placement in schools, to contribute to our understanding of this important student learning process. Method: Action research was used across four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…These authors associated students’ difficulty when responding spontaneously to unforeseen events during client assessments with the concept of reflection-in-action, considered foundational to on-the-spot experimentation (Schon, 1987). Similarly, Dancza et al (2019) drew on the categories of knowledge identified by Billet (2010) to describe the differences between role emerging and traditional placements in students’ learning pace and reliance on their own reasoning. This was associated with the more limited access to profession-specific knowledge during role emerging placements than in traditional placements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors associated students’ difficulty when responding spontaneously to unforeseen events during client assessments with the concept of reflection-in-action, considered foundational to on-the-spot experimentation (Schon, 1987). Similarly, Dancza et al (2019) drew on the categories of knowledge identified by Billet (2010) to describe the differences between role emerging and traditional placements in students’ learning pace and reliance on their own reasoning. This was associated with the more limited access to profession-specific knowledge during role emerging placements than in traditional placements.…”
Section: Resultsmentioning
confidence: 99%
“…Research involving primary data collection was conducted in the following countries: Australia (4), Canada (2), America (2), United Kingdom (1), Switzerland (1), and South Africa (1). Locations for primary data collection were often referred to broadly as placements without specifying the setting or clinical population, except for a university-based paediatric clinic (Copley et al, 2011;Copley et al, 2010) and schools (Dancza et al, 2019;Dancza et al, 2016;Kaelin & Dancza, 2019). Participant groups included practice educators, university educators, new graduates and, most commonly, students.…”
Section: Resultsmentioning
confidence: 99%
“…Time and space was created by practice educators so students could try out their ideas and learn from the consequences. Students gained confidence as they saw the results of their input and were able to learn from their ‘mistakes’ in a controlled and supervised environment 9 . This supportive learning space was achieved through practice educators offering emotional support, but also challenging students to analyse, reflect and make their own decisions about their practice.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of helpful learning and supervisory approaches generated from one cycle was applied and tested in subsequent cycles, adding depth and richness to the results. The results of the larger study relating to the development of a workbook supporting student's learning and the student learning processes are reported elsewhere 8,9 . This article focuses on the supervisory experiences of students and practice educators.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore a variety of placement models can have benefits such as better awareness of other professional roles, increased placement capacity; increased skills for the established workforce; students enabled to work with specialist and emerging fields of practice and students better prepared for registration (O'Leary and Bromley 2009;McClimens et al 2013;Harrison-White & King, 2015). Whilst Role Emerging Placements have grown in popularity for allied healthcare students (Dancza et al 2019) this is a novel approach to nurse education. An alternative placement experience was designed at one HEI to resolve some of the challenges identified above.…”
Section: Introductionmentioning
confidence: 99%